Persepsi Siswa tentang Kompetensi Mengajar Mahasiswa Program Pengalaman Lapangan Kependidikan (PPLK) di Kelas XI SMK Negeri 1 Sumatera Barat - Putra, Kevinda; Fernanda, Yolli; Abadi, Zainal; Andri, Junil (TSAQOFAH, 2025)
This study is motivated by the importance of evaluating the teaching competencies of students participating in the Teaching Practice Field Experience Program (PPLK) as an integral component in enhancing the quality of future educators. The purpose of this research is to describe students’ perceptions of the teaching competencies of PPLK students from the Faculty of Engineering, Universitas Negeri Padang, who conducted teaching practice in Grade XI at SMK Negeri 1, West Sumatra. A descriptive method with a quantitative approach was used. Data were collected through a closed-ended questionnaire using a four-point Likert scale, covering a single variable: student perception. This variable was measured through four indicators: teaching skills, knowledge, physical condition, and personality of the PPLK students. The research population consisted of all students in the Mechanical Engineering department, with simple random sampling employed for sample selection. Validity testing was conducted using the Product Moment correlation, and reliability was tested using Cronbach’s Alpha, assisted by SPSS version 25. Data were analyzed descriptively and presented as percentages. The results indicate that students’ perceptions of PPLK students’ teaching competencies fall within the "very good" category, with a percentage of 77.66%. These findings suggest that PPLK students were able to conduct the teaching and learning process effectively and were positively received by students. The implications of this study are expected to contribute to the development of a more systematic and high-quality PPLK program.